Increased Body Weight and Fat Mass After Subchronic GIP Receptor Antagonist, but Not GLP-2 Receptor Antagonist, Administration in Rats - Baldassano, Sara; Gasbjerg, Lærke Smidt; Kizilkaya, Hüsün Sheyma; Rosenkilde, Mette Marie; Holst, Jens Juul; Hartmann, Bolette (Frontiers in Endocrinology, 2019)
Glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-2 (GLP-2) are hormones secreted from the enteroendocrine cells after a meal. They exert their actions through activation of G protein-coupled receptors (R), the GIPR and GLP-2R, respectively. Both have been reported to influence metabolism. The purpose of the study was to investigate the role of the hormones in the regulation of lipid and bone homeostasis by subchronic treatment with novel GIPR and GLP-2R antagonists. Rats were injected once daily with vehicle, GIPR, or GLP-2R antagonists for three weeks. Body weight, food intake, body composition, plasma lipoprotein lipase (LPL), adipokines, triglycerides and the marker of bone resorption carboxy-terminal collagen crosslinks (CTX), were examined. In rats, subchronic treatment with GIPR antagonist, rat GIP (3-30)NH2, did not modify food intake and bone resorption, but significantly increased body weight, body fat mass, triglycerides, LPL, and leptin levels compared with vehicle treated rats. Subchronic (Pro3)GIP (a partial GIPR agonist), GLP-2(11-33) and GLP-2(3-33) (GLP-2R antagonists) treatment did not affect any parameter. The present results would be consistent with a role for GIP, but not GLP-2, in the maintenance of lipid homeostasis in rats, while neither GIPR nor GLP-2R antagonism appeared to influence bone resorption in rats.